Case Studies of Family Expressed Emotion for Persons Living with Schizofrenia in Delta State of Nigeria - Ewhrudjakpor, Christian (European Journal of Mental Health, 2009)
This study is aimed at assessing family expressed emotions as a predictor of health status of family members living with schizophrenia as well as identifying some characteristics for high or low emotions of family members towards a ‘sick’ member. There were thirty-one families with members suffering from schizophrenia as diagnosed by psychiatrists (using DSM-IV-TR) in government owned hospitals. They were judgmentally sampled with the assistance of social workers. The instrument for gathering data was a validated modified Camberwell Family Interview (CFI) schedule reflecting three major areas: Hostility, Critical comments, and Over-involvement of expressed emotions of family members. The procedure was using trained research assistants from the area to conduct these interactive sessions in their lingua franca. The data generated was subjected to qualitative analysis which shows that out of the 31 families studied, 25 or 80.65% had high expressed emotions while six families or 19.35% had low expressed emotions. However, only five ‘sick’ members had not experienced a relapse since the first treatment and discharge. Seven ‘sick’ members were vagrant of the 25 high expressed emotion families. The study revealed that expressed emotions significantly determine the number of relapses of the member living with schizophrenia; that the gender of a ‘sick’ member does in fact determine the level of expressed emotion from family members. The study also revealed that the poverty of families or shame for families from low and high socio-economic backgrounds respectively are motives for emotions expressed. A model of family therapy was proffered.